Carbohydrate ingestion induces differential autonomic dysregulation in normal-tension glaucoma and primary open angle glaucoma. - Lei Cao; Stuart L Graham; Paul M Pilowsky (PLoS ONE)
Background It is reported that glaucoma may be associated with vascular dysregulation. Normal tension glaucoma (NTG) and primary open angle glaucoma (POAG), which feature different intraocular pressure levels, may manifest differential features of systemic autonomic dysregulation. Methods and results We investigated autonomic regulation to carbohydrate ingestion and postural change in 37 glaucoma patients (19 NTG and 18 POAG) and 36 controls. Subjects were age and gender-matched, normotensive, and had normal comparable insulin sensitivity. Continuous finger arterial pressure and ECG was recorded in supine and standing positions before and after carbohydrate ingestion. Low frequency (LF, 0.04-0.15Hz) and high frequency (HF, 0.15-0.4Hz) spectral power of heart rate and systolic blood pressure variability (HRV and SBPV) were calculated to estimate sympathovagal function. Overall comparison glaucoma (N = 37) and controls (N = 36) showed an increased sympathetic excitation, vagal withdrawal and unstable mean arterial pressure after carbohydrate ingestion in glaucoma patients. Glaucoma severity by retinal nerve fibre layer (RNFL) thickness is positively correlated to autonomic responses (HRV LF power and HF power in normalised units (nu), and HRV LF/HF ratio) after carbohydrate ingestion. Early (30 minutes) following carbohydrate ingestion, SBP LF power and HRV parameters remained unchanged in controls; while POAG showed abnormal autonomic responses, with a paradoxical vagal enhancement (increased HRV HF power in nu) and sympathetic inhibition (decreased HRV LF power nu and HRV LF/HF ratio), and associated hypotension. Later (60-120 minutes) following carbohydrate ingestion, HRV parameters remained unaltered in controls; whereas NTG manifested vagal withdrawal (reduced HRV HF power nu) and sympathetic hyper-responsiveness (increased HRV LF power nu and HRV LF/HF ratio), despite increased SBP LF power in both controls and NTG. Both NTG and POAG exhibited attenuated autonomic responses to postural stress. Conclusions NTG and POAG both manifest some systemic autonomic cardiovascular dysregulation. However, the two forms of glaucoma respond differentially to carbohydrate ingestion, irrespective of insulin resistance.